Butterfly Species Richness in Selected West Albertine Rift Forests - Kasangaki, Patrice; Akol, Anne M.; Isabirye Basuta, Gilbert (International Journal of Zoology, 2012)
The butterfly species richness of 17 forests located in the western arm of the Albertine Rift in Uganda was compared using cluster analysis and principal components analysis (PCA) to assess similarities among the forests. The objective was to compare the butterfly species richness of the forests. A total of 630 butterfly species were collected in 5 main families. The different species fell into 7 ecological groupings with the closed forest group having the most species and the swamp/wetland group with the fewest number of species. Three clusters were obtained. The first cluster had forests characterized by relatively high altitude and low species richness despite the big area in the case of Rwenzori and being close to the supposed Pleistocene refugium. The second cluster had forests far away from the supposed refugium except Kisangi and moderate species richness with small areas, whereas the third cluster had those forests that were more disturbed, high species richness, and low altitudinal levels with big areas.